Ukraine in the process of European integration: the economic aspect - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (Instytut Europeistyki, Warszawa, 2015)
The article examines the current trends, problems and prospects of Ukraine development in the terms of European integration processes. Particular attention is paid to the European integration in the economic sphere. The basic indicators of economic development of Ukraine are given in the article. The authors notice that the way of Ukraine to the European Union determines fundamental principles of foreign and internal policy of Ukraine. And the integration of Ukraine into the EU will provide its entry to the world’s most powerful regional association, which significantly affects the overall dynamics, structural changes, the level of technology and the format of the regulation of the global economy.

Artykuł analizuje aktualne trendy, problemy i perspektywy rozwoju Ukrainy w zakresie europejskich procesów integracyjnych. Szczególną uwagę przywiązuje się do integracji europejskiej w sferze gospodarczej. Artykuł odnosi się również do podstawowych wskaźników rozwoju gospodarczego Ukrainy. Autorzy zauważają, że podstawowe cele polityki zagranicznej i wewnętrznej Ukrainy są determinowane przez jej drogę do Unii Europejskiej. Integracja z UE pozwoliłaby Ukrainie na wejście do struktury o wyjątkowym znaczeniu w regionie, co znacząco wpłynęłoby na ogólną dynamikę tego państwa, zmiany strukturalne, poziom technologii i kształt współpracy z zakresu gospodarki światowej.
Keywords: domestic economy; economy development; the process of European integration; reforms; Ukraine; the European Union; gospodarka krajowa; rozwój ekonomiczny; proces integracji europejskiej; reform; Ukraina; Unia Europejska